The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1590/0102-311x00214919
|View full text |Cite
|
Sign up to set email alerts
|

Fatores sociodemográficos e clínicos associados ao tempo para o início do tratamento de câncer de cólon e reto no Brasil, 2006-2015

Abstract: O câncer de cólon e reto apresenta alta incidência mundialmente, porém a letalidade da doença é maior em países em desenvolvimento. O objetivo deste estudo é analisar fatores sociodemográficos e clínicos associados ao atraso para o início de tratamento de câncer de cólon e reto em hospitais no Brasil. Trata-se de estudo retrospectivo com dados dos registros hospitalares de câncer no Brasil de 2006 a 2015. O desfecho analisado é o tempo para início do tratamento de câncer de cólon e reto e possíveis associações… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
10

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 28 publications
0
10
0
10
Order By: Relevance
“…There is some evidence that younger adults with CRC experience different interval lengths compared to older adults. Our review showed time from diagnosis to treatment can be short among younger adults, and several studies have shown this interval is significantly shorter compared to older patients [ 31 , 38 , 46 , 81 ]. Lima et al [ 81 ] reported the odds of the treatment interval being greater than 60 days were significantly higher among those aged 50–59 compared to age <40 (OR 1.32, 95% CI 1.07–1.64; adjusted for race, education, marital status, stage and municipality).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…There is some evidence that younger adults with CRC experience different interval lengths compared to older adults. Our review showed time from diagnosis to treatment can be short among younger adults, and several studies have shown this interval is significantly shorter compared to older patients [ 31 , 38 , 46 , 81 ]. Lima et al [ 81 ] reported the odds of the treatment interval being greater than 60 days were significantly higher among those aged 50–59 compared to age <40 (OR 1.32, 95% CI 1.07–1.64; adjusted for race, education, marital status, stage and municipality).…”
Section: Discussionmentioning
confidence: 95%
“…Our review showed time from diagnosis to treatment can be short among younger adults, and several studies have shown this interval is significantly shorter compared to older patients [ 31 , 38 , 46 , 81 ]. Lima et al [ 81 ] reported the odds of the treatment interval being greater than 60 days were significantly higher among those aged 50–59 compared to age <40 (OR 1.32, 95% CI 1.07–1.64; adjusted for race, education, marital status, stage and municipality). Redaniel et al [ 46 ] similarly showed in an adjusted analysis that patients aged 55–64 experienced an additional 2.92 days (95% CI 1.76–4.08) for the treatment interval compared to patients 15–44 years, increasing to an additional 3.76 days (95% CI 2.58–4.93) for those aged 65–74.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…De acordo com os resultados deste estudo, o sexo feminino apresentou maior prevalência de tratamento oportuno. Embora isso tenha sido corroborado por estudos anteriores 9,26 , as diferenças de tempo entre os sexos são mais pujantes no período anterior ao diagnóstico, em que os homens tendem a negligenciar mais os sintomas e postergar a procura por atendimento médico, em virtude de um modelo de masculinidade idealizada, no qual se associa a figura masculina à resistência a doenças e ao menor cuidado de si 13,27,28 .…”
Section: Discussionunclassified